1997
DOI: 10.1590/s0102-33061997000100010
|View full text |Cite
|
Sign up to set email alerts
|

Mucorales (Zygomycotina) da Mata Atlântica da Reserva Biológica do Alto da Serra de Paranapiacaba, Santo André, SP

Abstract: Treze táxons de Mucorales (Zygomycotina), distribuídos num total de 266 registros, foram isolados de folhas de Alchornea triplinervia (Spreng.) Müll. Arg. colocadas em ambientes terrestre e aquático, e de amostras de solo e de água de riacho, coletadas mensalmente, de julho de 1988 a maio de 1990 na Reserva Biológica do Alto da Serra de Paranapiacaba, no município de Santo André, SP. As espécies que apresentaram os maiores números de registro de ocorrência foram Mucor hiemalis Wehmer (78 registros), Mucor circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
1
5
0
Order By: Relevance
“…This manuscript reports ecological data regarding the communities of Mucorales in DOF, TAB, SAN and MAN ecosystems located in Pernambuco, Brazil. Most of the mucoralean species isolated in the present study have already been reported in other inventories of Atlantic Forest soil (Eicker 1969;Varghese 1972;Ogbonna & Pugh 1982;Rambelli et al 1984;Bettuci & Roquebert 1995;Schoenlein-Crusius et al 1996;Schoenlein-Crusius & Milanez 1997;Schoenlein-Crusius & Milanez 1998;Schoenlein-Crusius et al 2006;Maia et al 2006;Lima et al 2018a). However, seven new records for this domain are reported herein: Absidia sp., Cunninghamella bertholletiae, C. elegans, Gongronella brasiliensis, Lichtheimia ramosa, Mucor indicus, and M. irregularis, which represent an addition of almost 10 % of the currently known species in the Brazilian Atlantic Forest for which 66 species of Mucorales are currently recorded (Flora do Brasil 2020).…”
Section: Discussionsupporting
confidence: 78%
“…This manuscript reports ecological data regarding the communities of Mucorales in DOF, TAB, SAN and MAN ecosystems located in Pernambuco, Brazil. Most of the mucoralean species isolated in the present study have already been reported in other inventories of Atlantic Forest soil (Eicker 1969;Varghese 1972;Ogbonna & Pugh 1982;Rambelli et al 1984;Bettuci & Roquebert 1995;Schoenlein-Crusius et al 1996;Schoenlein-Crusius & Milanez 1997;Schoenlein-Crusius & Milanez 1998;Schoenlein-Crusius et al 2006;Maia et al 2006;Lima et al 2018a). However, seven new records for this domain are reported herein: Absidia sp., Cunninghamella bertholletiae, C. elegans, Gongronella brasiliensis, Lichtheimia ramosa, Mucor indicus, and M. irregularis, which represent an addition of almost 10 % of the currently known species in the Brazilian Atlantic Forest for which 66 species of Mucorales are currently recorded (Flora do Brasil 2020).…”
Section: Discussionsupporting
confidence: 78%
“…In the "Parque Estadual das Fontes do Ipiranga", in the municipality of São Paulo, a study of the diversity of Mucorales in soil samples, during eleven months, resulted in the identification of 21 taxa (73) and a survey conducted in the "Reserva Biológica de Paranapiacaba" yielded 13 species of Mucorales (55). The highest number of Mucorales taxa was obtained from the soil followed by the leaf litter ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In the same area, an evaluation of diversity of a soil submitted to high quantities of bird's excrements yielded seven zoosporic fungi, 22 anamorphs, 19 Mucorales and one Ascomycota (41,60). In the preserved forest of the "Reserva Biológica de Paranapiacaba" the study of the fungal succession on Alchornea triplinervia leaves in the terrestrial and aquatic environments resulted in the isolation of 20 zoosporic fungi, 82 anamorphs, 20 Mucorales and eight Ascomycota, a total of 123 fungal taxa (55)(56)(57)(58). Comparison of the aquatic mycota on submerged leaves of Ficus microcarpa L. f., Quercus robur L. and Alchornea triplinervia in a same stream, permitted the observation of 20 zoosporic fungi and 11 aquatic Hyphomycetes (59).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mucor circinelloides and M. hiemalis are among the most common taxa of Mucorales isolated from soil (Domsch et al 2007) and have been reported in Brazilian Atlantic Forest ecosystems (Schoenlein-Crusius and Milanez 1997;Schoenlein-Crusius et al 2006; Diversity of Mucorales in natural and degraded semi-arid soils 2008). These species are now reported for the first time in the Brazilian Caatinga domain, including Caatinga s.s., Sandy Caatinga and Carrasco ecosystems.…”
Section: Discussionmentioning
confidence: 99%